1992
DOI: 10.1068/p210147
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Integration of Spatially Filtered Visual Images

Abstract: Factors which govern the temporal integration of spatial information were examined in a group of five experiments. A series of high-pass and low-pass spatially filtered versions of a visual scene were generated. Observers' ratings of these filtered versions of the scene for perceived image quality indicated that quality was determined both by the bandwidth of spatial information and the presence of high-spatial-frequency edge information. When sequences of three different versions of the scene were presented o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
109
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 22 publications
13
109
5
Order By: Relevance
“…For the anisotropic-integration hypothesis, the integration order is fixed and the majority of empirical data indicates that LSFs are integrated faster than HSFs (Hughes, Fendrich & ReuterLorenz, 1990;Hughes, Nozawa & Kitterle, 1996;LaGasse, 1993;Parker, Lishman & Hughes, 1992Watt, 1987Watt, , 1988, though one study found that HSFs were integrated faster (McSorley & Findlay, 2002). Bachmann (1987) showed two target images (an eye with an eyebrow and a face) mixed up with eight images of different objects.…”
Section: Empirical Evidence Supporting the Hypothesis Of Anisotropic mentioning
confidence: 99%
See 1 more Smart Citation
“…For the anisotropic-integration hypothesis, the integration order is fixed and the majority of empirical data indicates that LSFs are integrated faster than HSFs (Hughes, Fendrich & ReuterLorenz, 1990;Hughes, Nozawa & Kitterle, 1996;LaGasse, 1993;Parker, Lishman & Hughes, 1992Watt, 1987Watt, , 1988, though one study found that HSFs were integrated faster (McSorley & Findlay, 2002). Bachmann (1987) showed two target images (an eye with an eyebrow and a face) mixed up with eight images of different objects.…”
Section: Empirical Evidence Supporting the Hypothesis Of Anisotropic mentioning
confidence: 99%
“…Although Parker, Lishman and Hughes (1992) found empirical support for the anisotropic hypothesis using a procedure that involved displaying a three-image sequence containing different frequencies of the same scene, shown for an exposure time of 40 ms, they also argued that the task (judging the quality of an image) was not precise enough and it probably would have been better to ask to the subjects to perform direct discriminations. Hence, Parker, Lishman and Hughes (1997) tested subjects' ability to classify full-bandwidth images into coarse-to-fine and fine-to-coarse sequences containing distorted versions of the originals, i.e.…”
Section: Face Perception 21mentioning
confidence: 99%
“…In higher-level vision, numerous studies have examined how luminance cues supported the recognition of faces (Breitmeyer, 1984;Costen, Parker, & Craw, 1994;Fiorentini, Maffei, & Sandini, 1983;Sergent, 1986), objects (Parker et al, 1996), and scenes Parker, Lishman, & Hughes, 1992;Schyns & Oliva, 1994). It was found that fine-scale boundary edges (from high spatial frequencies) and coarser scale blobs (from low spatial frequencies) could selectively mediate different categorizations of the same stimuli (e.g., Schyns & Oliva, 1999).…”
Section: Luminance Color and Recognitionmentioning
confidence: 99%
“…On this third axis, each resolution of the image represents a different spatial scale (in the figure, there are two such spatial scales). studies have dealt with scale-specific recognition of real-world visual displays (though see, e.g., Costen, Parker & Craw, 1994;Hayes, Morrone & Burr, 1986;Parker, Lishman, & Hughes, 1992). In fact, many visual recognition studies (especially those using simple line-drawings of stimuli, e.g., Biederman, 1988;Boyce, Pollatsek, & Rayner, 1989) implicitly assume that important processing mostly occurs at finer resolutions.…”
Section: Coarse-to-fine Recognitionmentioning
confidence: 99%
“…The claim is that a temporal delay between low and high spatial frequency channels (i.e. coarse processing precedes fine processing) would explain the precedence of global information (e.g., Breitmeyer, 1984;Ginsburg, 1986;Parker et al, 1992;Marr, 1982; among many others). However, the psychological literature has often neglected an important difference between global and local processing on one hand, and scale perception on the other.…”
Section: Coarse-to-fine Recognitionmentioning
confidence: 99%